Solid state switch based pulsers for the injection system of the collider VEPP-2000 - Grishanov, B.I.; Podgorny, F.V.; Kasaev, A.S. (Вопросы атомной науки и техники, 2004)
We describe high voltage pulsers for supplying the kickers of the collider VEPP-2000 injection system. The high voltage pulse is formed as a result of a sharp break of a high current, accumulated previously in storage elements, by means of a SOS-diode The generator scheme is described too.